(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This research explores the growing role of international norms particularly treaties and conventions—as a source of constitutional legitimacy within modern legal systems, with a specific focus on Iraq. It examines the legal implications of conflicts between international agreements and national constitutions and analyzes the scope of the Federal Supreme Court’s authority in protecting civil, political, economic, social, and cultural rights. The study highlights the need to align Iraqi constitutional provisions with international commitments to enhance human rights protection through effective constitutional oversight.